2019
DOI: 10.1029/2018jb017008
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐Mode Strain Localization Generated by Hydration Reaction at Crustal Conditions

Abstract: Hydration reactions influence rock density and rheology. For example, volume increases produced in hydration reactions may generate sufficient tensile and shear stress to fracture both the rock undergoing the reaction and the surrounding host rock. We performed in situ dynamic X-ray synchrotron microtomography experiments to investigate reaction-induced fracturing. Two experiments on hydration of periclase were performed at 180 or 190°C, under a confinement of 10 or 80 MPa, a pore fluid pressure of 5 or 75 MPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…They also reproduce a complex three-dimensional fracturing pattern often referred to as a mesh structure in serpentines. However, Zheng et al (2019) showed that when the effective pressure applied to the sample exceeds about 30 MPa, the periclase (MgO) to brucite (Mg(OH) 2 ) reaction-induced fracturing process slows dramatically. Such slowing with increasing the confining pressure has also been observed in the hydration of CaO into Ca(OH 2 ) (Wolterbeek et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also reproduce a complex three-dimensional fracturing pattern often referred to as a mesh structure in serpentines. However, Zheng et al (2019) showed that when the effective pressure applied to the sample exceeds about 30 MPa, the periclase (MgO) to brucite (Mg(OH) 2 ) reaction-induced fracturing process slows dramatically. Such slowing with increasing the confining pressure has also been observed in the hydration of CaO into Ca(OH 2 ) (Wolterbeek et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This reaction created a force of crystallization that fractured the peridotite. This image was acquired under in situ conditions using synchrotron X‐ray microtomography and the Hades triaxial rig (Zheng et al., 2019). (d and e) Numerical simulations of the hydration reaction of an elliptic grain that leads to an increase of volume and the formation of radial fractures in the surrounding rock (reproduced from Yoshida et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The co‐occurrence of mechanical features predicted by both end‐member modes is called “mixed‐mode” fracturing (Rubin, 1995) and was found both in natural outcrops (e.g., Dering, Micklethwaite, Cruden, et al, 2019; Martinez‐Poza & Druguet, 2016) and laboratory experiments of fluid intrusion in natural rock samples (e.g., Zheng et al, 2019). Mechanical indicators of LEFM, such as tapered intrusion fronts and cavities, were found in some cases in association with dike opening profiles that depart from the parabolic shape expected in elastic materials (Daniels et al, 2012; Vachon & Hieronymus, 2017) and blunt intrusion tips and shear‐mode fractures.…”
Section: Magma Emplacement Modelsmentioning
confidence: 99%
“…However, experiments are limited in size to a few centimeters, owing to scanner dimensions, and in the speed of flow they can capture. For instance, Zheng et al. (2019) performed a reactive flow experiment in which water percolated through a porous rock sample (a cylinder 5 mm in height an 2.3 mm in diameter) and the reaction induced fracturing of the sample.…”
Section: Current Measurement Techniques Used To Study Geological Flowmentioning
confidence: 99%